The level of knowledge and attitude towards dengue fever among medical students of Udayana University, Bali, Indonesia in 2018 - Agilan Sethupathy; I Made Sudarmaja; Luh Ariwati (Intisari Sains Medis, 2019)
Background: There is a lot of impact of dengue among youngsters and also adults. The virus infects human blood and causes a migraine-like headache, rash, achiness, queasiness, tiredness and fever. Severe dengue can cause organ damage, severe bleeding, dehydration and even death. So, this study aims to know the level of knowledge and attitudes towards dengue infection among medical students from Faculty of Medicine, Universitas Udayana, Bali, IndonesiaMethods: A cross-sectional study was conducted among 99 respondents by using a valid and reliable self-questionnaires to assess the participants‘ knowledge and attitude about dengue fever. Knowledge is the ability to answer correctly towards Dengue related questions. Knowledge was evaluated based on 20 questions grouped under the following three categories. The attitude was assessed based on the ability of participants to give correct answers to 14 questions on attitude towards dengue. After that, the data were analysed using SAS software package version 9.1.Results: There was 43% were men and 56% of women enrolled in this study. Most of them are aged 18 years old (69.7%), followed by 19 years old (23.2%), and 17 years old (6.1%). The average age was 18.15 + 0.5 years old. All of the participants (100%) answered that they would go to the doctor they get the dengue infection. Around 94,9% of them stated that they would drink a lot of water if they get dengue fever, and 89,9% of them said they would get a lot of rest. The vast majority of participants use insecticide (86,9%), curtains (84,8%), mosquitoes net (81,8%), cover their water storage (98,0%) and try to not hoard stuff in their home (90,9%).Conclusion: The recent findings suggest that most students know the symptoms, transmission, and how to manage dengue fever. The attitudes of participants toward dengue infection have been assessed, and all answered that they would go to the doctor if they get the dengue infection